1966
DOI: 10.1039/tf9666200801
|View full text |Cite
|
Sign up to set email alerts
|

Investigation by infra-red spectroscopic methods of deuterium exchange properties of aerosil silicas

Abstract: The characteristics of the residual band at 365Ocm-1 in the infra-red spectrum of deuterated aerosils have been determined. The band corresponds to hydroxyl groups and not to molecular water. It is assigned to interacting hydroxyls sited on neighbouring silicon atoms within the solid lattice of the silica particles. The effects of annealing the solid on the intensity of the residual band are described and a mechanism proposed for the removal of the corresponding species. The rehydration or chemisorption phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

1970
1970
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 1 publication
2
10
0
Order By: Relevance
“…Many applications of silicas and modified silicas rely on their unique surface properties, which in turn are largely determined by the concentration, distribution, and nature of hydroxyl groups (silanols) on the surface. Various spectroscopic techniques, including NMR, infrared, ,, and Raman 16,17,27,32,57-59 spectroscopies, as well as chemical probes ,,,,− ,, ,,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many applications of silicas and modified silicas rely on their unique surface properties, which in turn are largely determined by the concentration, distribution, and nature of hydroxyl groups (silanols) on the surface. Various spectroscopic techniques, including NMR, infrared, ,, and Raman 16,17,27,32,57-59 spectroscopies, as well as chemical probes ,,,,− ,, ,,…”
Section: Introductionmentioning
confidence: 99%
“…IR spectroscopy can resolve isolated (non-hydrogen-bonded) silanols from clustered (hydrogen-bonded) silanols and physisorbed water on a silica surface 29-56 and has been useful for studying the characteristics of surface silanols as a function of temperature, although the results have not been entirely conclusive. , , ,, 1 H NMR experiments based on the CRAMPS (combined rotation and multiple-pulse spectroscopy) technique can resolve isolated silanols from hydrogen-bonded silanols on the silica surfaces and have indicated that the only silanols on a silica surface that has been heated under vacuum at 500 °C are isolated silanols. ,,, Unfortunately, 1 H CRAMPS spectra cannot directly resolve single silanols from geminal silanols. On the other hand, solid-state 29 Si NMR spectroscopy, using magic-angle spinning (MAS) with or without cross-polarization (CP), has clearly established the presence of both geminal and single silanols and has shown that both geminal and single silanols are major hydroxyl components on various silica surfaces that have been evacuated at various temperatures. ,,, Overall, the combination of IR, 1 H CRAMPS, and 29 Si NMR results indicates that isolated silanols on various silica surfaces can be single silanols or geminal silanols.…”
Section: Introductionmentioning
confidence: 99%
“…4), adsorption and subsequent outgassing were adsorption height). Re-deuteration also only has a small effect on the intensity of the absorption band near to 3.9 ~i (which is assigned to vicinal surface groups (13), and the spectrum is only marginally different to the final trace presented in Fig. 46.…”
Section: Fig 4 (A)mentioning
confidence: 86%
“…4. The spectra presented demonstrate that adsorption of n-butylamine is indeed primarily associated with the isolated surface hydroxyl sites because of the perturbation of the absorption band at 2.67 p (3.63 p, deuterated) which is assigned to those groups (4,5,(11)(12)(13) ( b ) Irreversibly adsorbed n-butylamine on pressed silica disc (pretreated at 810 "C), and its loss with increasing outgas temperature. Trace I , initial spectrum of disc; trace 2, after exposure to amine vapor at 20 T, followed by outgassing r) at 30 "C; trace 3, subsequent outgas at 65 "C; trace 4, subsequent outgas at 95 "C, trace 5, subsequent outgas at 140 "C.…”
Section: Isolafed Hydroxyl Are Defined Asmentioning
confidence: 99%
“…In the OH region, only a broad band around 3530 cm -1 decreased on addition of 40 mTorr of BF3 (spectrum 1), which means that hydrogen-bonded OH groups were used for the formation of the species A, B, and C. No decrease was observed in intensity of the 3746 cm -1 band due to the isolated OH groups, as also pointed out by Morrow et al 6 The remaining broad band centered around 3660 cm -1 is due to inaccessible OH groups which do not take part in any reaction with molecules. 4,[9][10][11][12][13] The degree of the increase was larger than that of the decrease in the region of 1600 -1300 cm -1 after the addition of BF3. This is because the species A that formed first was transformed to the species B and C at a larger rate than that of the transformation of gaseous BF3 to the species A.…”
Section: Cases Of Bf3 With Low Pressure and 473-k-preheated Silicamentioning
confidence: 99%